Pengaruh Dukungan Sosial Terhadap Resiliensi Pada Mantan Pecandu Narkoba - Laksana, Silviani Ollvia; Virlia, Stefani (Psychopreneur Journal, 2019)
The aim of this study is to measure the effect of social support on resilience to former drug addict. The hypothesis of this study is there is a positive social support to resilience to former drug addict. The study was conducted 50 former drug addict. This study used quantitative method with a type of correlational research. Date were collected using social support scale and resilience scale. The scale of social support in this study using the MPSS scale by Zimet (1988) and the scale of resilience in this study using the CD-RISC scale by Connor and Davidson (2003). The results showed that there was a positive social support to resilience to former drug addict with results (R = 0,604, p <0,05). This result implied the higher social support received by individual, the higher the resilience that they will have and vice versa.